2018
DOI: 10.1002/adfm.201800388
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Fluctuations and Structural Heterogeneities in Metallic Glasses

Abstract: Suppressing crystallization of a metallic melt results in a disordered solid, also known as a metallic glass. One may conclude that a metallic glass is free of defined structural length scales beyond some atomic-scale value that characterizes short-and medium-range order. While it is well known from atomistic modeling that a metallic glass is structurally heterogeneous, heterogeneities at such a small length scale can hardly be resolved in experiments. This review highlights experimental insights into elastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 226 publications
(360 reference statements)
0
25
0
Order By: Relevance
“…One obvious reason for this is the difficulty in revealing and characterizing a nano-scale sheared region in a disordered material. In the context of structural heterogeneities of metallic glasses, this has been summarized in detail in a recent review article, [61] and we will here only highlight a few aspects regarding the fluctuations of both length scales and structural measures of shear bands.…”
Section: B Effective Barrier Energies Across Numerous Alloy Systemsmentioning
confidence: 99%
“…One obvious reason for this is the difficulty in revealing and characterizing a nano-scale sheared region in a disordered material. In the context of structural heterogeneities of metallic glasses, this has been summarized in detail in a recent review article, [61] and we will here only highlight a few aspects regarding the fluctuations of both length scales and structural measures of shear bands.…”
Section: B Effective Barrier Energies Across Numerous Alloy Systemsmentioning
confidence: 99%
“…The design of novel strategies and optimization of thermal and mechanical treatments of metallic glasses is important for accessing a broad range of states with improved physical and mechanical properties [1]. It is generally accepted that an elementary plastic event in disordered solids involves a collective rearrangement of a small group of atoms or a shear transformation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…With tip sizes down to the nanometer scale, the tip-sample interaction can be analyzed in local regions to reveal the mechanical properties of the interaction volume. For example, elastic heterogeneity has been intensively studied in recent years [7] and found to occur on a length scale of <10 nm, in good agreement with TEM observations [9]. By measuring tip-sample contact-resonance frequencies with atomic force acoustic microscopy (AFAM), Wagner et al found heterogeneities in the local modulus of a PdCuSi MG which are much larger in magnitude than in its crystalline counterpart [8].…”
Section: Heterogeneities Of Mechanical Propertiesmentioning
confidence: 70%
“…Beyond the feature of missing long-range order, the amorphous structure of MGs has been found to be heterogeneous rather than homogenous [5,6]. Both structure and mechanical properties have been found to be different in different regions of MGs on length scales ranging from the nanoscale to the microscale [7]. So far, heterogeneities have been found in the modulus [8], density [9,10], and relaxation behavior [11].…”
Section: Introductionmentioning
confidence: 99%